Pengaruh Pemberian Zeolite dan Dosis Pupuk Nitrogen Terhadap Pertumbuhan Vegetatif Jagung (Zea mays, L.) di Media Pasir Pantai - Gunawan Budiyanto; Mulyono Mulyono; Fiyoni Dwi Setyawan (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
A research to study the effects of Zeolite and nitrogen fertilizer application on vegetative growth of maize crop in coastal sandy soil was conducted on the research field of Agriculture Faculty, Muhammadiyah University of Yogyakarta at Tamantirto, Bantul District of Yogyakarta during October until February, 2003. This research was aimed on the study of Zeolite application in order to enhance the nitrogen uptake in the coastal sandy soil, and its effects on vegetative growth of CP I variety of maize. The pot experiment was arranged in 7 x 3 factorial completely randomized design, with 4 replications. The first factor was Zeolite dosage consisted of 7 levels, i.e:  0, 3, 4, 5, 6, 7, and 8 %; and the second one was 3 levels nitrogen fertilizer dosage which consisted of: 75, 110, and 145 kg/ ha. The nitrogen fertilizer was applied on the medium mixed with Zeolite granules. Observations on plant height, stem diemeter, leaves number, plant fresh and dry weight were done during the vegetative growth of maize. The results showed that Zeolite application significantly enhanced the vegetative growth of CPI maize. The 5,2  - 5,6  % Zeolite was optimum to gave the maximum growth of maize crop. Nitrogen fertilizer application was also significantly increased the plant height and biomass weight, and the 145 kg/ha was the optimum dosage. There was no interaction between Zeolite and nitrogen fertilizer application in order to affected the maize growth.